Multifunctional Single‐Crystallized Carbonate Hydroxides as Highly Efficient Electrocatalyst for Full Water splitting. Issue 20 (6th April 2018) - Hui, Lan; Xue, Yurui; Jia, Dianzeng; Yu, Huidi; Zhang, Chao; Li, Yuliang
Abstract: The controllable synthesis of single‐crystallized iron‐cobalt carbonate hydroxide nanosheets array on 3D conductive Ni foam (FCCH/NF) as a monolithic oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) bifunctional electrocatalyst for full water splitting is described. The results demonstrate that the incorporation of Fe can effectively tune the morphology, composition, electronic structure, and electrochemical active surface area of the electrocatalysts, thus greatly enhancing the intrinsic electrocatalytic activity. The optimal electrocatalyst (F0.25 C1 CH/NF) can deliver 10 and 1000 mA cm −2 at very small overpotentials of 77 and 256 mV for HER and 228 and 308 mV for OER in 1.0m KOH without significant interference from gas evolution. The F0.25 C1 CH‐based two‐electrode alkaline water electrolyzer only requires cell voltages of 1.45 and 1.52 V to achieve current densities of 10 and 500 mA cm −2 . The results demonstrate that such fascinating electrocatalytic activity can be ascribed to the increase in the catalytic active surface area, facilitated electron and mass transport properties, and the synergistic interactions because of the incorporation of Fe. Abstract : Multifunctional single‐crystallized iron‐cobalt carbonate hydroxides grown on nickel foam (F x C1 CH/NF) with high‐efficiency oxygen evolution reaction, hydrogen evolution reaction as well as full water splitting activities in alkaline media are demonstrated by controllable tuning of their morphological, compositional, and electric properties. The incorporation of Fe in the cobalt carbonate hydroxides leads to improved catalytic activity and long‐term stability.